Point of Pines, Arizona : a history of the University of Arizona Archaeological Field School - Haury, Emil W. (Emil Walter), 1904-1992 (Anthropological papers of the University of Arizona, 1989)
Recalls education and daily life at Point of Pines and also provides the background for the scientific papers that have resulted from the research that was undertaken there. Appendixes list contributions to Point of Pines archaeology, staff members and students, and institutions represented by attendees.